Exploring Caring Motivation Barriers among Mothers of Children with Intellectual and Developmental Disabilities: A Qualitative Content Analysis - Seyed Javad Hosseini; Monir Ramezani; Farah Ashrafzadeh; Jamshid Jamali (International Journal of Community Based Nursing and Midwifery)
Background: Caring a child with intellectual and developmental disabilities (IDDs) presents numerous challenges that can impact the mothers’ caring motivation. This study aimed to explore the caring motivation barriers among mothers of children with IDDs.Methods: This qualitative content analysis study was conducted from July 2023 to March 2024. Twenty-six mothers of children with IDDs were purposefully selected to participate in face-to-face semi-structured interviews. Data collection continued until saturation was achieved. Data analysis was conducted using Mayring’s inductive approach within MAXQDA version 20. We utilized Lincoln and Guba’s criteria for ensuring rigor.Results: The mean ages of the mothers and children were 40.34±7.44 years and 9.38±4.33 years, respectively. The analysis identified several main categories and 15 subcategories: (I) Mother’s insufficient readiness: low level of competency, decreased maternal strength with child’s advancing age, caregiving fatigue, complex health problems, and incompatibility with the child’s disability; (II) Perceived lack of support for the mother in caregiving: insufficient family support, inadequate social support, deficient healthcare provider support, lack of spiritual support, and insufficient financial support; and (III) Encountering caring complexity: disappointment with the child’s recovery, challenges in providing optimal rehabilitation, multiple physical problems in the child, unintentional behaviors in the child, and priority of personal goals over the care.Conclusion: The motivation of mothers to care for children with IDDs is influenced by a range of challenges. Future research should take these barriers into account to enhance maternal caregiving motivation. To modify the identified obstacles, a comprehensive plan of actions should be devised.